Semi-custom IC design and VLSI - Hicks, P. J. (Peter J.) (London Peter Peregrinus Ltd., 1983)
The following topics are dealt with: IC design; VLSI; silicon fabrication; bipolar technologies; MOS technologies; semi-custom integrated circuits; circuit design; programmable logic array; ROM; CAD; and design automation.
Also available in print version.
Electronic reproduction.
Keywords: Integrated circuits -- Very large scale integration; Electronic books